1995
DOI: 10.1210/endo.136.8.7628399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen and progesterone on luteinizing hormone-releasing hormone messenger ribonucleic acid levels: consideration of temporal and neuroanatomical variables.

Abstract: We examined temporal effects of estradiol (E2) and progesterone on cellular levels of LHRH messenger RNA (mRNA) in several brain regions. Female rats were ovariectomized and implanted with SILASTIC brand capsules of oil or E2 1 week later (day 0). Progesterone capsules were implanted on the morning of day 2. Using in situ hybridization histochemistry, we found that on day 2, E2 induced a complex temporal pattern of changes in LHRH mRNA levels. Levels in ovariectomized E2-treated animals were lower than control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Using in situ hybridization to quantitate gene expression, several groups [22, 23, 24] have also demonstrated that estradiol replacement decreases GnRH gene expression in the ovariectomized rat during the morning hours when the negative feedback action of estradiol on gonadotropin secretion is manifest [25]. An inhibitory action of estradiol on GnRH gene expression at this phase of the light-dark cycles, however, has not always been a universal finding in the rat [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using in situ hybridization to quantitate gene expression, several groups [22, 23, 24] have also demonstrated that estradiol replacement decreases GnRH gene expression in the ovariectomized rat during the morning hours when the negative feedback action of estradiol on gonadotropin secretion is manifest [25]. An inhibitory action of estradiol on GnRH gene expression at this phase of the light-dark cycles, however, has not always been a universal finding in the rat [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using modified stainless steel needles, the rMPN (17 gauge), SCN (21 gauge), and cortex (17 gauge) were microdissected and stored at Ϫ80°C until processed. The organun vasculosum of the lamina terminalisrMPN contains the subpopulation of GnRH neurons that regulate LH secretion (Swanson, 1987;Petersen et al, 1995). We chose to examine these areas based on previous work showing that VIP predominately innervates the GnRH neurons in this region and that GnRH neurons that are lateral to these regions were not included (van der Beek et al, 1997;Krajnak et al, 2001) Stereotaxic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…However, steroids have not been shown to affect secretion of GnRH from GT1–7 cells and E2 caused a slight but significant inhibition of GnRH gene expression [55]. This is in contrast to the stimulatory effect of E2 on GnRH gene expression [56, 57, 58, 59, 60, 61]and secretion [8]in vivo supporting our proposal that E2 acts to induce GnRH through actions on astrocytes found in vivo but not present in the GT1–7 cultures.…”
Section: Discussionmentioning
confidence: 99%